Analisis Beban Kerja Terhadap Kinerja Karyawan - Dyna Arofatul Baiyinah (Prosiding, 2025)
Workload is a few tasks given by the company to employees; workload is one of the things that affects employee performance. Company X is a company involved in manufacturing, has 45 employees. The purpose of this study is to determine and analyze the workload of the production department in Company X, the high workload given affects the realization of production results. This study method uses quantitative and is analyzed using the Structural Equation Modeling - Partial Least Squares) SEM PLS method. The results of the study show that the workload that occurs in Company X, can have a positive influence on employee performance with work standards that encourage employees to achieve the results that have been achieved